Peliosanthes yangchunensis (Asparagaceae), a new species from Guangdong, China - Feng, Hui-Zhe; Wu, Rang-Min; Zeng, Qiu-Gen; Fan, Qiang; Liao, Wen-Bo (Phytotaxa, 2024)
A new species named Peliosanthes yangchunensis are described, which is endemic to Yangchun, western Guangdong, South China. The new species is closely related to P. macrostegia, but differs from the latter in that the flowers smaller, star-like and with strongly revolute, spreading and narrowly oblong tepals, style conical, ovary hexagonal in cross section, and fruit ovoid-globose, flower period September to October. Comparisons with other closely related species are also provided.